Piano music by Viktoria Poleva: Experience of performing embodiment - Starodub, Iryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the study. The main characteristic identifiers of Victoria Poleva’s compositional style are considered, in particular, the dominant piano component of the music worldview, which translates the main ideas and meanings in the spiritual and instrumental genres of oeuvre. The actual factors of the special study of the meaningfulness of the texture embedded in the piano within the style of "sacred minimalism" are highlighted. The main performance specifics of the works were found to be close to the correct understanding in the construction of the interpretive version. The piano work of the composer has not been scientifically studied, the lack of competent analytical works prompts the study "Music for the Piano" (author’s name), which is a sought-after and popular repertoire. Scientific investigations of this matter will reveal one of the bright styles of modern music art in the field of musicology and cultural studies. For the first time in home-bred art history, the main stylistic guidelines, image-emotional, programmatic priorities were identified, and the majority of piano music material was examined and analyzed. The chosen aspect of the research is under the spotlight of modern, global, concert life. The main objective of the study. The purpose of the article is to reveal the artistic meanings-messages of the composer, the peculiarities of their concert performance, the role of meaningful interpretation of piano reception. The methodology. Empirical research method was used from the experience of numerous performances of Viktoria Poleva’s works, the analytical method reveals the essence of the actual problem; the comparative method consists in comparing the interpretive versions of pianists’ performance live, and by comparing them in video and audio recordings, it allows presenting modern performance trends; the source method in the form of archival notes, newspaper publications, posters, work with manuscript scores argues the basis of the outlined aspect; relying on citations during communication with the author brings the research result closer to reliability. Results and conclusions. It has been proven that the author’s philosophical and artistic messages hit the listener’s reactions-impressions through her performing skills during live music performances. The top priority role of a pianist’s training is emphasized. The importance of world performances of compositions that reflect the author’s spiritual quest is explained in terms of restoring the man’s balance and harmony in response to the today’s cruel challenges. The author substantiates the means of music expressiveness in the piano presentation, which serve to achieve the goal-affect, as the main idea of focusing on powerful manifestations of aesthetic impression. Attention is focused on special, technical and artistic piano techniques that enhance sound effects, and with the help of which the main essence of the composer’s ideas is expressed. Significance. The piano music of V. Poleva is gaining widespread worldwide popularity, the score music is mostly in the state of manuscripts and needs publication, the topic of piano works is relevant for future scientific research.